Label-free Dengue E protein detection using a functionalized tapered optical fiber sensor - Mustapha Kamil Y.; Abu Bakar M.H.; Mustapa M.A.; Yaacob M.H.; Abidin N.H.Z.; Syahir A.; Lee H.J.; Mahdi M.A. (Elsevier B.V., 2023)
Diagnosis; Fiber optics; Optical fibers; Optical sensors; Proteins; Viruses; Clinical management; Dimensional changes; Fundamental concepts; Optical based sensors; Quantitative assessments; Recombinant antibody; Tapered optical fiber sensors; Tapered optical fibers; Fibers